A Simple and Efficient Protocol of RNA Extraction from Apple Leaves (Malus x domestica); A Silica Column-Based Method - Siti Zulaeha; Anna Safarrida; Agus Suyono; Endah Dwi Hartuti; Devit Purwoko; Teuku Tajuddin (International Journal of Agriculture System, 2023)
Extracting total RNA from plant tissue using the conventional isolation method is time-consuming, requires expensive reagents and produces low-quality RNA. Over time, researchers have used many commercial RNA extraction kits on silica column-based to obtain high-quality RNA so that the isolated RNA can further use for sequencing and quantitative PCR analysis. This study aimed to identify the efficient apple leaf extraction method with high concentration and good quality RNA extraction. In this study, we applied four isolation kits to extract RNA from apple leaves, such as NucleoSpin® RNA Plant Kit (Macherey-Nagel), Quick-RNA™ Miniprep Kit (Zymo Research), PureLink® RNA Mini Kit (Ambion), and RibospinTM Plant Kit (GeneAll). The results showed that apple leaves RNA isolation successfully using the RibospinTM Plant Kit (Geneall) reagent with a concentration of 59.9±12.3 ng/µl in good RNA integrity. So, these isolated RNA can be used for further analysis.